RELATIONSHIP WITH SELF-CONCEPT IN ADOLESCENT ANXIETY CLASS VII, VIII, IX IN COUNTRY MTs SREBEGAN CEPER KLATEN - Linda Dewi Rivayani; Suwarno .; Witriyani . (STIKES DUTAGAMA KLATEN, 2014)
Background: Teenage is a period of transition or the transition from childhood into adulthood. At this time, adolescents undergo various changes, changes that seem obvious are physical changes and is accompanied by development of reproductive capacity. Changes that occur in the affecting teens view themselves. Self-concept in adolescents more emphasis on appearance; nose, large ears, short stature, or body frame is large resulting in poor adolescents assessed against him. Anxiety is often caused because teenagers are not able to adapt and think the reality of the changes that occur as the body shape changes, the development of secondary sex characteristics and roles. Purpose: To determine the relationship of self-concept and anxiety in adolescent girls at MTs Srebegan Methods: Quantitative research, descriptive research design to study the correlation. The study design was cross-sectional. The sampling technique used is proportionate stratified sampling. The sample was student of class VII, VIII and IX MTs Srebegan Ceper Klaten by 65 respondents. Results: The relationship of self-concept with anxiety were analyzed using chi-square (X2) with a confidence level of 95% or α = 0.05 obtained X2 value of 14.841 count. X2 price table with df = 2 at 5.991 then X2 count is greater than the table (14.841> 5.991) and p-value = 0.001 is less than the value of alpha (α = 0.05) which means that the alternative hypothesis (Ha) that can interpreted that there is a significant negative relationship between self-concept and anxiety in adolescent girls in Srebegan MTs. Conclusion: The negative relationship between self-concept and anxiety in adolescent girls can be interpreted more positive self-concept will be more mild anxiety in adolescent girls.